Long term results of compression therapy alone versus compression plus surgery in chronic venous ulceration (ESCHAR): randomised controlled trial. Issue 7610 (1st June 2007) - Gohel, Manjit S; Barwell, Jamie R; Taylor, Maxine; Chant, Terry; Foy, Chris; Earnshaw, Jonothan J; Heather, Brian P; Mitchell, David C; Whyman, Mark R; Poskitt, Keith R
Abstract : Objective To determine whether recurrence of leg ulcers may be prevented by surgical correction of superficial venous reflux in addition to compression. Design Randomised controlled trial. Setting Specialist nurse led leg ulcer clinics in three UK vascular centres. Participants 500 patients (500 legs) with open or recently healed leg ulcers and superficial venous reflux. Interventions Compression alone or compression plus saphenous surgery. Main outcome measures Primary outcomes were ulcer healing and ulcer recurrence. The secondary outcome was ulcer free time. Results Ulcer healing rates at three years were 89% for the compression group and 93% for the compression plus surgery group (P=0.73, log rank test). Rates of ulcer recurrence at four years were 56% for the compression group and 31% for the compression plus surgery group (P<0.01). For patients with isolated superficial reflux, recurrence rates at four years were 51% for the compression group and 27% for the compress plus surgery group (P<0.01). For patients who had superficial with segmental deep reflux, recurrence rates at three years were 52% for the compression group and 24% for the compression plus surgery group (P=0.04). For patients with superficial and total deep reflux, recurrence rates at three years were 46% for the compression group and 32% for the compression plus surgery group (P=0.33). Patients in the compression plus surgery group experienced a greater proportion of ulcer free time after three years compared with patients in the compression group (78% v 71%; P=0.007, Mann-Whitney U test). Conclusion Surgical correction of superficial venous reflux in addition to compression bandaging does not improve ulcer healing but reduces the recurrence of ulcers at four years and results in a greater proportion of ulcer free time. Trial registration Current Controlled Trials ISRCTN07549334 .